Human, animal and environmental contributors to antibiotic resistance in low-resource settings: integrating behavioural, epidemiological and One Health approaches. Issue 1876 (11th April 2018) - Rousham, Emily K.; Unicomb, Leanne; Islam, Mohammad Aminul
Abstract : Antibiotic resistance (ABR) is recognized as a One Health challenge because of the rapid emergence and dissemination of resistant bacteria and genes among humans, animals and the environment on a global scale. However, there is a paucity of research assessing ABR contemporaneously in humans, animals and the environment in low-resource settings. This critical review seeks to identify the extent of One Health research on ABR in low- and middle-income countries (LMICs). Existing research has highlighted hotspots for environmental contamination; food-animal production systems that are likely to harbour reservoirs or promote transmission of ABR as well as high and increasing human rates of colonization with ABR commensal bacteria such as Escherichia coli . However, very few studies have integrated all three components of the One Health spectrum to understand the dynamics of transmission and the prevalence of community-acquired resistance in humans and animals. Microbiological, epidemiological and social science research is needed at community and population levels across the One Health spectrum in order to fill the large gaps in knowledge of ABR in low-resource settings.